2017
DOI: 10.3390/nano7060133
|View full text |Cite
|
Sign up to set email alerts
|

Parameters for Fabricating Nano-Au Colloids through the Electric Spark Discharge Method with Micro-Electrical Discharge Machining

Abstract: In this study, the Electric Spark Discharge Method (ESDM) was employed with micro-electrical discharge machining (m-EDM) to create an electric arc that melted two electrodes in deionized water (DW) and fabricated nano-Au colloids through pulse discharges with a controlled on–off duration (TON–TOFF) and a total fabrication time of 1 min. A total of six on–off settings were tested under normal experimental conditions and without the addition of any chemical substances. Ultraviolet–visible spectroscopy (UV–Vis), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Nanometal colloids, such as nanogold, nanosilver, nano-copper, nano-aluminum, and nano-titanium, can be made with any method able to conduct electricity using an EDM [ 26 , 27 , 28 , 29 , 30 ]. Nanosilver colloids have been applied in biomedical research, and silver ions can resist bacteria growth.…”
Section: Methodsmentioning
confidence: 99%
“…Nanometal colloids, such as nanogold, nanosilver, nano-copper, nano-aluminum, and nano-titanium, can be made with any method able to conduct electricity using an EDM [ 26 , 27 , 28 , 29 , 30 ]. Nanosilver colloids have been applied in biomedical research, and silver ions can resist bacteria growth.…”
Section: Methodsmentioning
confidence: 99%
“…The toxicity is likely due to one or more of the following: cellular rate of uptake, increase in cell membrane permeability, changes to nanoparticle size and morphology, altered dispersion or agglomeration and rate of dissolution. It has been reported that NPs can be prepared using an electrical discharge [44][45][46]. We therefore investigated the effect of CAP on AgNP.…”
Section: The Effect Of Cap On Agnp Sizementioning
confidence: 99%
“…With the increasing market demand for miniaturization and the precision of products, micro-processing technology has become one of the important indicators to measure a country's scientific and technological strength [1][2][3]. Micro-electrical discharge machining (micro-EDM) has become one of the most popular microfabrication technologies due to the advantage of machining electrically conductive materials without direct contact [4][5][6]. Micro-EDM has been has attracted great attention from researchers and has been widely used in the micro-machining field [7][8][9].…”
Section: Introductionmentioning
confidence: 99%